The Influence of Online Gaming on the Learning Activities of Senior High School Students: A Case Study - Hukama, Nadhif Syahmi; Hadi, Muhammad S.; Iswat, Habibi; Fedro, Alfarid; Fathurrahman, Arif Fatahilah (OMNICODE Journal (Omnicompetence Community Developement Journal), 2025)
Games are commonly played for entertainment, leisure, and recreational purposes. Among adolescents, online games have become especially popular, offering both potential benefits and challenges. While some studies highlight their role in enhancing cognitive skills, collaboration, and motivation, excessive gaming can also negatively impact academic performance and time management. This study aimed to examine the influence of online gaming on the learning activities of senior high school students. Data were collected through using structured questionnaires, semi-structured interviews, observations and distributed to 18 tenth-grade students at Thursina IIBS. The findings indicate that although many students engage in popular titles such as Mobile Legend (Mobile Legends: Bang Bang), PUBG: Battlegrounds (PlayerUnknown’s Battleground), EA SPORTS™ FIFA Mobile Soccer, eFootball™ 2024 (Konami), Roblox, Race Master 3D – Car Racing, Brawl Stars, and Grand Theft Auto V (GTA V), the overall effect of gaming on learning activities depends largely on how students manage their time. Most respondents reported being able to balance gaming with study responsibilities, suggesting that online gaming does not necessarily hinder learning outcomes when moderated appropriately.